Forward-looking information disclosure determinants and effects on earnings management : pre-during-post international financial reporting standards era-evidence from publicly listed companies in malaysia - Almhuob Muftah, Imad Hamd (2024)
The current study addresses four research objectives: 1) exploring Forward-looking Information Disclosure (FLID) practices in Malaysia, 2) identifying the determinants of FLID, 3) examining the relationship between FLID and Earnings Management (EM), and 4) assessing the moderating effect of IFRS on the FLID-EM connection. To achieve these objectives, the study uses computerised content analysis to collect FLID data, manual content analysis for governance data from annual reports, and the financial data collected from the Refinitiv Datastream database. The sample includes publicly listed companies on Bursa Malaysia, covering nine years (2009-2017) and all industries except financial firms and those that did not adopt IFRS in 2012, results in 1,971 firm-year observations. The research employs a robust dynamic estimation approach (System GMM) to control for endogeneity sources like unobserved heterogeneity, reverse causality, simultaneity, and dynamic endogeneity. Regarding the first objective, the study finds significant increases in various FLID proxies, indicating a growing willingness among Malaysian companies to share future information, peaking in 2017. Most FLID topics, except for employee-related FLID, show steady increases, particularly in 2016 and 2017. Operational FLID is disclosed at higher levels with variations across the years while accounting and employee FLID remain comparatively low. The Health Care industry demonstrates the highest level of future-oriented disclosure, followed by the Utilities industry, whereas the Industrial Products and Property industries show the lowest levels. The Sys-GMM estimator results indicate that in Malaysia, larger board sizes and board independence are associated with lower levels of FLID, suggesting that in Malaysia, external directors might be chosen based on personal connections. Additionally, firm size and accruals EM positively impact FLID. However, the study finds no evidence supporting a significant effect of the other determinants. The findings indicate a positive and significant relationship between FLID and both EM proxies (accruals and real activities EM) in Malaysia, suggesting that managers who increase future-oriented disclosure also manipulate earnings. This supports the opportunistic behaviour perspective over agency and signalling theories in the Malaysian context. Additionally, IFRS adoption moderates the relationship between FLID and accruals EM, weakening its positive impact and thus constraining accruals EM practices, aligning with the hypotheses and theories. However, IFRS adoption does not significantly affect the relationship between FLID and real activities EM. The study makes several contributions to the FLID literature. First, it examines FLID and its relationship to EM in a robust dynamic setting addressing various sources of endogeneity. Second, it provides the first evidence of the relationship between FLID and real activities EM. Third, it examines the impact of IFRS mandatory adoption on the FLID-EM link. Finally, it offers the first evidence of the FLID-EM nexus in Southeast Asia, particularly Malaysia. The study findings have significant implications. It highlights key methodological considerations for researching FLID and EM. Researchers should consider issues stemming from dynamic endogeneity between FLID and other factors, such as, but not limited to, corporate governance attributes, firm profitability, and EM. For investors and accounting setters, it reveals the potential risks of FLID driven by opportunistic managers. Regulators and policymakers, especially in Malaysia and developing economies, should note that larger boards and independent directors may be less effective. This suggests a need to reconsider corporate governance codes and guidelines concerning FLID reporting in the narratives of annual reports. Additionally, non-IFRS-adopting countries might improve financial disclosure quality by adopting IFRS